IoT-based smart garden monitoring and automated irrigation system using NodeMCU - Mohd Zulkefli, Muhammad Afiq Aiman; Shafie, Rosmawati; Hassan, Nurhaffizah; Ahmed, Norizan; Mohd Norzeli, Syamimi (UiTM Press, 2025)
This paper describes the development of a monitoring and controlling system for a garden using the Internet of Things (IoT). The system is designed to assist users in managing their plants and gardens remotely and effectively. Soil moisture levels are difficult to assess and manage, and achieving their target levels can be challenging. Therefore, an automatic water pump system is the optimal solution for this situation. The soil moisture sensor measures the moisture content in the soil, and the system automatically turns on the water pump when the moisture level is insufficient for healthy plant growth. A Light Emitting Diode (LED) is used to notify the user when the water pump is operating. A NodeMCU is used as the microcontroller for this project, which has a built-in Wi-Fi module, making it easier to interface with the Blynk software on a smartphone. The input is a soil moisture sensor, and the outputs are a water pump and an LED. The system successfully demonstrated real-time monitoring and automated control of soil moisture, ensuring optimal plant health. The integration of NodeMCU with Blynk enabled seamless remote access and notifications, enhancing user convenience. Experimental results confirmed the system's reliability in maintaining soil moisture levels within the desired range, reducing manual intervention, and improving water efficiency. This IoTbased approach provides a practical and scalable solution for smart gardening applications.